Impact of access to microfinance services on farm households’ income in Iringa region, Tanzania - Mapesa, Haruni Jeremia (Sokoine University of Agriculture, 2024)
A thesis submitted in fulfillment of the requirements for the degree of doctor of philosophy of Sokoine University of Agriculture Morogoro, Tanzania.